AKTIVITAS ANTIOKSIDAN, KADAR FENOLIK, DAN KADAR FLAVONOID TOTAL DAUN JATI CINA (Senna alexandrina) - Khoirul Ngibad (UIN AR-RANIRY, 2023)
Free radicals are unstable molecules or chemical fragments with one or more unpaired electrons that can cause organ damage, resulting in chronic and degenerative disorders. Antioxidant substances can reduce the effects of free radicals. Chinese teak (Senna alexandrina) leaves, which include flavonoids and phenols, are one source of natural antioxidants. The purpose of this study is to extract Chinese teak leaf powder with ethanol and measure the levels of flavonoids and total phenolics. Furthermore, the antioxidant activity of an ethanol extract of Chinese teak leaves was investigated. After soaking Chinese teak leaf powder in ethanol, the filtrate is condensed using a rotary evaporator. Total phenolic and flavonoid levels are measured using UV-Vis spectrophotometry. The diphenyl-1-picrylhydrazyl (DPPH) technique is used to determine antioxidant activity. The yield of the ethanol extract of Chinese teak leaves was 3.3%, with flavonoids and total phenolics values of 7.94 mg QE/g and 7.9 mg GAE/g, respectively. Each test solution demonstrated antioxidant activity of 20, 40, 80, and 100 mg/L, with the greatest activity at 100 mg/L having a percent inhibition value of 83%.